2024
DOI: 10.1177/10870547231225818
|View full text |Cite
|
Sign up to set email alerts
|

In Memoriam: Professor Joseph Biederman’s Contributions to Child and Adolescent Psychiatry

Stephen V. Faraone,
Jeffrey H. Newcorn,
Janet Wozniak
et al.

Abstract: Objective: To provide an overview of Joe Biederman’s contributions to child and adolescent psychiatry. Method: Nine colleagues described his contributions to: psychopharmacology, comorbidity and genetics, pediatric bipolar disorder, autism spectrum disorders, Tourette’s and tic disorders, clinical and neuro biomarkers for pediatric mood disorders, executive functioning, and adult ADHD. Results: Joe Biederman left us with many concrete indicators of his contributions to child and adolescent psychiatry. He set u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 292 publications
(386 reference statements)
0
4
0
Order By: Relevance
“…In addition, over 50% of children with the aforementioned disorders (ADHD, ASD, and SLD) also present symptoms of Developmental Coordination Disorder (DCD) [ 8 ]. Finally, according to [ 9 ], up to 50% of children with comorbid NDDs also present Tourette’s syndrome symptoms, often leading to temper tantrums, insomnia, obsessive–compulsive disorder, self-injuries, mood disorders, and oppositional defiant disorders or conduct disorders. All these conditions further inhibit the children’s overall functioning and emotional state [ 10 ].…”
Section: The High Rates Of Comorbidity Among Nddsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, over 50% of children with the aforementioned disorders (ADHD, ASD, and SLD) also present symptoms of Developmental Coordination Disorder (DCD) [ 8 ]. Finally, according to [ 9 ], up to 50% of children with comorbid NDDs also present Tourette’s syndrome symptoms, often leading to temper tantrums, insomnia, obsessive–compulsive disorder, self-injuries, mood disorders, and oppositional defiant disorders or conduct disorders. All these conditions further inhibit the children’s overall functioning and emotional state [ 10 ].…”
Section: The High Rates Of Comorbidity Among Nddsmentioning
confidence: 99%
“…Various other studies reported a high prevalence of ADHD in children and adolescents with tic disorders (e.g., Tourette’s syndrome) [ 40 ], while much higher rates of other disorders, including obsessive–compulsive disorder (OCD), oppositional defiant disorder (ODD), insomnia, mood disorders, were also found to be comorbid with ADHD [ 9 , 40 ].…”
Section: Attention Deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%
See 2 more Smart Citations